Long-term results after traumatic knee joint dislocations. Issue 4 (27th April 2017) - Ull, Christopher; Seybold, Dominik; Königshausen, Matthias; Schildhauer, Thomas; Geßmann, Jan
Aims and Objectives: : Traumatic knee joint dislocations belong to the most serious injuries of the lower extremity with a high rate of neurovascular injuries, soft tissue injuries and compartment syndromes. The aim of the study was to determine the long-term results of patients with traumatic knee joint dislocations after conservative and operative treatment of the ligaments. In addition, differences between the two therapies were investigated and what kind of incidents and complications occurred. Materials and Methods: : All patients with traumatic knee joint dislocation were included over a time period of 25 years (1990 to 2014). 119 patients with 121 traumatic knee joint dislocations were hospitalized during this time. A conservative treatment of the ligaments was performed in 48 knee joint dislocations (39.7%) and an operative treatment in 73 injuries (60.3%). After an average follow-up of 10.9 ± 6.7 years, 38 patients with 39 knee joint dislocations were examined. Significance was set to p < 0.05. Results: : Patients with operative ligament care showed significantly better flexion compared to patients with conservative treatment of the ligaments (p < 0.033). A median of 76 points (range 34 - 100 points) was achieved in the Lysholm score. 56.2 points (range 45.3 - 71.1 points) were achieved in the SF-36 mental health score and 43.7 points (range 21.2 - 59.6 points) in the SF-36 physical heatlh score. The subjective part of the IKDC 2000 showed a median score of 60.9 points (range 32.1 - 97.7 points). Patients with operative ligament care showed better results in the scores, however, without achieving any significance.Posttraumatic arthrosis was found in 47% of all radiologically-re-examined patients in the Kellgren-Lawrence score. Conclusion: : The long-term results showed a satisfactory knee function with physical limitations in the health-related quality of life. However, a reduced range of motion as well as a posttraumatic osteoarthritis of the affected knee joint often appeared, which was independent of the therapy strategy. Patients with operative ligament care showed better results in the scores without any significane, but achieved a significantly better flexion than patients with conservative treatment of the ligaments.